Effect of the Bifidobacterium animalis Subsp. Lactis, BB-12® on Cronobacter sakazakii Growth in Infant Formulas with Different Acid-Buffering Capacities - Anthimia Batrinou; Efstathia Tsakali; Vassilia J. Sinanoglou; Polyvakidi Maria Eleni; Katerina Pyrovolou; Arhontoula Chatzilazarou; Spyros J. Konteles (Applied Sciences)
The opportunistic pathogenic bacterium C. sakazakii poses a significant infection risk to infants through contaminated powdered infant formulae (PIFs) when proper hygiene and temperature control are neglected during reconstitution. This study aimed to investigate whether the acid-buffering capacity (ABC) of commercially available PIFs enriched with the probiotic strain Bifidobacterium animalis subsp. lactis (BB-12®) could influence the growth of C. sakazakii. Two PIFs differing in their ABC were reconstituted (RIF), inoculated, and incubated in monoculture and co-culture at 22 °C and 37 °C for 24 h. After 24 h of incubation at 22 °C, regardless of the ABC type of PIF, the population of C. sakazakii in the monoculture was approx. 1.4 log cycles higher than the inoculum, while, in the co-culture, the C. sakazakii count was approx. 0.34 log cycles lower. In contrast, at 37 °C during the 24 h co-culture in the lower ABC infant formula, C. sakazakii was <10 CFU/mL. In all co-culture samples, the pH was significantly lower (p < 0.05) in the PIF with the lower ABC. An analysis of the weak organic acids at 12 and 24 h of incubation revealed that the antimicrobial activity is significantly affected by the final pH value, the type of the weak organic acids, and their ionic–non-ionic ratio, which is formed through the common ion effect.